Framing Naturalisasi Pemain Sepak Bola Indonesia: Studi Komparatif Kompas.Com dan Bola.Net - Yogi Purwanto (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study aims to analyze how two online media, Kompas.com and Bola.net, frame the issue of naturalization of Indonesian football players in the 2022–2024 period. This study applies a qualitative approach with framing analysis based on the Pan and Kosicki model to four news items from each media as the unit of analysis. Using the framing analysis approach developed by Pan and Kosicki, this study reveals how the construction of reality regarding naturalized players is formed through narrative choices, language styles, and thematic focuses of each media. The results of the analysis show that Kompas.com tends to present naturalization as a positive strategy to improve the performance of the national team, with a neutral to supportive frame. In contrast, Bola.net emphasizes the dramatic aspects and public responses, including controversies and criticisms of the policy. The differences in framing reflect different editorial orientations, while also showing how the media plays an active role in shaping public perceptions regarding the issue of naturalization of football players.